Synthesis and in vitro evaluation of Ca2 + channel blockers 1, 4-dihydropyridines analogues against Trypanosoma cruzi and Leishmania amazonensis: SAR analysis. Issue 6 (December 2017) - Pollo, Luiz A.E.; de Moraes, Milene H.; Cisilotto, Júlia; Creczynski-Pasa, Tânia B.; Biavatti, Maique W.; Steindel, Mario; Sandjo, Louis P.
Abstract: Drugs containing the1, 4-dihydropyridine (DHP) core have recently attracted attention concerning their antiparasitic effect against various species of Leishmania and Trypanosoma . This approach named drugs repositioning led to interesting results, which have prompted us to prepare 21 DHP's analogues. The 1, 4-DHP scaffold was decorated with different function groups at tree points including the nitrogen atom (NH and N -phenyl), the aryl group attached to C-4 (various substituted aryl residues) and the carbon atoms 2 and 6 (bearing Ph or Me groups). Moreover, the products were evaluated for their cytotoxicity on three cancer and a non-tumoral cell lines. Only 6 of them were antiproliferative and their weak effect (CC50 comprised between 27 and 98 μM) suggested these DHPs as good candidates against the intracellular amastigote forms of L. amazonensis and T. cruzi . L. amazonensis was sensitive to DHPs5, 11 and15 (IC50 values at 15.11, 45.70 and 53.13 μM, respectively) while 12 of them displayed significant to moderate trypanocidal activities against T. cruzi . The best trypanocidal activities were obtained with compounds2, 18 and21 showing IC50 values at 4.95, 5.44, and 6.64 μM, respectively. A part of the N -phenylated DHPs showed a better selectivity than their NH analogues towards THP-1 cells. 4-Chlorophenyl, 4-nitrophenyl and 3-nitrophenyl residues attached to the carbon atom 4 turned to be important sub-structures for the antitrypanosomal activity. Graphical abstract: Highlights: Synthesis of 21 Ca 2 + channel blocker 1, 4-dihydropyridine analogues Evaluation of their antiparasitic effects against T. cruzi and L. amazonensis 4 of the 12 active compounds revealed promising IC50 values on T. cruzi . L. amazonensis was sensitive to three of the prepared 1, 4-dihydropyridines.